A nickel-based corrosion-resistant alloy resistant to high temperature creep and a method for manufacturing the same

By adding graphene coated tungsten carbide and performance synergists to the nickel-based corrosion-resistant alloy, a nickel-based corrosion-resistant alloy that resists high-temperature creep is prepared, which solves the problem that traditional nickel-based corrosion-resistant alloys are prone to creep deformation in high-temperature environments and improves its application performance in high-temperature and high-pressure environments.

CN119020638BActive Publication Date: 2025-05-02无锡腾达海川新材料有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411136522.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-05-02
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

Traditional nickel-based corrosion-resistant alloys are prone to creep deformation in high temperature environments, affecting their stability and reliability in long-term use, resulting in a shortened service life, and limiting their application in harsh environments such as high temperature and high pressure.

Method used

By mixing nickel powder, chromium powder, iron powder, molybdenum powder, graphene coated tungsten carbide, titanium powder, aluminum powder and silicon powder evenly, ball milling and drying, followed by smelting, casting, heating and hot rolling forging, a nickel-based corrosion-resistant alloy that resists high temperature creep is prepared.

Benefits of technology

This method improves the strength, hardness and creep resistance of the alloy by adding graphene-coated tungsten carbide and performance synergists to the nickel-based corrosion-resistant alloy, extends its service life, and expands its application range in high temperature and high pressure environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004999580100000121
    Figure BDA0004999580100000121
Patent Text Reader

Abstract

The present invention relates to the field of nickel-based corrosion-resistant alloys, and specifically to a nickel-based corrosion-resistant alloy resistant to high-temperature creep and a method for manufacturing the same, which are used to solve the problem that conventional nickel-based corrosion-resistant alloys are prone to creep deformation in high-temperature environments, which affects their stability and reliability in long-term use and results in a shortened service life. The present invention adds graphene-coated tungsten carbide and a performance enhancer to the nickel-based corrosion-resistant alloy. The graphene-coated tungsten carbide improves the strength and hardness of the nickel-based corrosion-resistant alloy, while hindering the movement of dislocations and reducing deformation at high temperatures. The performance enhancer improves the fluidity and dispersibility of the components of the nickel-based corrosion-resistant alloy and improves the uniformity and compactness of the nickel-based corrosion-resistant alloy. Therefore, under the synergistic effect of the graphene-coated tungsten carbide and the performance enhancer, the nickel-based corrosion-resistant alloy is endowed with excellent mechanical properties, corrosion resistance and high-temperature creep resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nickel-based corrosion-resistant alloys, and in particular to a nickel-based corrosion-resistant alloy resistant to high-temperature creep and a manufacturing method thereof. Background Art

[0002] High temperature corrosion resistant alloy refers to a type of metal material based on nickel, iron or cobalt, which can withstand complex and harsh mechanical stresses and has good surface stability in high temperature environments. High temperature corrosion resistant alloys generally have high room temperature and high temperature strength, good oxidation resistance and hot corrosion resistance, excellent creep and fatigue resistance, and good organizational structure stability. Nickel-based corrosion resistant alloys are widely used in many industrial fields (such as aviation, aerospace, navigation, automobiles, flue gas desulfurization, denitrification, seawater desalination, nuclear industry, petroleum, and chemical industry) due to their excellent corrosion resistance and high temperature performance. However, with the continuous development of industrial technology, higher requirements are placed on the high temperature creep resistance of nickel-based corrosion resistant alloys. Traditional nickel-based corrosion resistant alloys are prone to creep deformation in high temperature environments, which affects their stability and reliability in long-term use, shortens their service life, and limits their application in some harsh environments such as high temperature and high pressure. Summary of the invention

[0003] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a nickel-based corrosion-resistant alloy resistant to high-temperature creep and a method for manufacturing the same: by uniformly mixing nickel powder, chromium powder, iron powder, molybdenum powder, graphene-coated tungsten carbide, titanium powder, aluminum powder and silicon powder to obtain a mixed powder material, adding the mixed powder material, performance enhancer and anhydrous ethanol to a ball mill for ball milling, and then drying to obtain a ball-milled powder material, melting the ball-milled powder material, and then casting to form an ingot, heating the ingot, and then hot rolling and forging to obtain a nickel-based corrosion-resistant alloy resistant to high-temperature creep, thereby solving the problem that traditional nickel-based corrosion-resistant alloys are prone to creep deformation in high-temperature environments, affecting their stability and reliability in long-term use, resulting in shortened service life, and limiting their application in some harsh environments such as high temperature and high pressure.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A nickel-based corrosion-resistant alloy resistant to high temperature creep, comprising the following components in parts by weight:

[0006] 50-55 parts of nickel powder, 17-21 parts of chromium powder, 24-28 parts of iron powder, 22-26 parts of molybdenum powder, 1-9 parts of graphene-coated tungsten carbide, 0.6-1.2 parts of titanium powder, 0.2-0.8 parts of aluminum powder and 0.1-0.5 parts of silicon powder;

[0007] Wherein, the graphene-coated tungsten carbide is prepared by the following steps:

[0008] Tungsten carbide and anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 25-35 minutes at an ultrasonic power of 300-350 W. Then, the reaction was stirred for 1-1.5 hours at a temperature of 25-30 ° C and a stirring rate of 300-400 r / min. After the reaction was completed, the reaction product was irradiated with a KrF excimer laser at an energy density of 0.8 J / cm 2 , irradiate for 20-30 minutes at a laser frequency of 10 Hz, then centrifuge, wash the precipitate with ethanol solution 2-3 times, then place it in a vacuum drying oven, and dry it at a temperature of 70-75°C for 3-5 hours to obtain graphene-coated tungsten carbide.

[0009] As a further solution of the present invention: the usage ratio of the tungsten carbide and anhydrous ethanol is 0.15g:50-60mL.

[0010] As a further solution of the present invention: the volume fraction of the ethanol solution is 70-80%.

[0011] As a further solution of the present invention: a method for manufacturing a nickel-based corrosion-resistant alloy resistant to high temperature creep, comprising the following steps:

[0012] Step 1: Weigh 50-55 parts of nickel powder, 17-21 parts of chromium powder, 24-28 parts of iron powder, 22-26 parts of molybdenum powder, 1-9 parts of graphene-coated tungsten carbide, 0.6-1.2 parts of titanium powder, 0.2-0.8 parts of aluminum powder and 0.1-0.5 parts of silicon powder according to weight parts, and set aside;

[0013] Step 2: Evenly mix nickel powder, chromium powder, iron powder, molybdenum powder, graphene-coated tungsten carbide, titanium powder, aluminum powder and silicon powder to obtain a mixed powder material;

[0014] Step 3: Add the mixed powder, performance enhancer and anhydrous ethanol into a ball mill, and mill for 2-3 hours at a ball milling rate of 300-400 r / min, and then dry to obtain a ball-milled powder;

[0015] Step 4: Melt the ball mill powder and then cast it to form an ingot;

[0016] Step 5: Heat the ingot at a temperature of 1150-1200°C for 8-10 hours, and then hot-roll and forge to obtain a nickel-based corrosion-resistant alloy that is resistant to high-temperature creep.

[0017] As a further solution of the present invention: the usage ratio of the mixed powder material, the performance enhancer and the anhydrous ethanol is 10kg:0.2-1.8kg:20-30L.

[0018] As a further solution of the present invention: the performance enhancer is prepared by the following steps:

[0019] Step a1: maleic anhydride, diethanolamine and p-toluenesulfonic acid are added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 20-30 min, then the temperature is raised to 60-65° C. and the stirring reaction is continued for 1-1.5 h. After the reaction is completed, the reaction product is cooled to room temperature to obtain an intermediate product A;

[0020] Step a2: adding mercaptopropionic acid, pentaerythritol, p-toluenesulfonic acid and toluene into a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stirring the mixture at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 15-25 min, then heating the mixture to 90-95° C. and continuing to stir the mixture for 6-8 h. After the reaction is completed, cooling the reaction product to room temperature, and then removing the solvent by rotary evaporation to obtain an intermediate product B;

[0021] Step a3: Add intermediate product A, intermediate product B, triethylamine and anhydrous tetrahydrofuran into a three-necked flask equipped with a stirrer, a thermometer, a gas duct and a reflux condenser, introduce nitrogen protection, stir the reaction for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then raise the temperature to reflux and continue stirring the reaction for 2-3 hours. After the reaction is completed, the reaction product is cooled to room temperature, then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a performance enhancer.

[0022] As a further solution of the present invention: the usage ratio of the maleic anhydride, diethanolamine and p-toluenesulfonic acid in step a1 is 10 mmol: 10 mmol: 0.01-0.03 g.

[0023] As a further solution of the present invention: the usage ratio of the mercaptopropionic acid, pentaerythritol, p-toluenesulfonic acid and toluene in step a2 is 45-50 mmol: 10 mmol: 0.03-0.07 g: 50-60 mL.

[0024] As a further scheme of the present invention: the usage ratio of the intermediate product A, the intermediate product B, triethylamine and anhydrous tetrahydrofuran in step a3 is 40-45mmol:10mmol:45-50mmol:80-100mL.

[0025] Beneficial effects of the present invention:

[0026] The present invention discloses a nickel-based corrosion-resistant alloy resistant to high-temperature creep and a manufacturing method thereof. The method comprises the following steps: uniformly mixing nickel powder, chromium powder, iron powder, molybdenum powder, graphene-coated tungsten carbide, titanium powder, aluminum powder and silicon powder to obtain a mixed powder material; adding the mixed powder material, a performance enhancer and anhydrous ethanol to a ball mill for ball milling, and then drying to obtain a ball-milled powder material; smelting the ball-milled powder material, and then casting to form an ingot; heating the ingot, and then hot rolling and forging to obtain a nickel-based corrosion-resistant alloy resistant to high-temperature creep; the present invention comprises adding graphene-coated tungsten carbide and a performance enhancer to the nickel-based corrosion-resistant alloy; Graphene-coated tungsten carbide improves the strength and hardness of nickel-based corrosion-resistant alloys, while hindering the movement of dislocations and reducing deformation at high temperatures. The performance enhancer improves the fluidity and dispersibility of the components of the nickel-based corrosion-resistant alloy, and improves the uniformity and density of the nickel-based corrosion-resistant alloy. Therefore, under the synergistic effect of graphene-coated tungsten carbide and performance enhancer, the nickel-based corrosion-resistant alloy is endowed with excellent mechanical properties, corrosion resistance and high-temperature creep resistance, and can be widely used in aviation, aerospace, navigation, automobiles, flue gas desulfurization, denitrification, seawater desalination, nuclear industry, petroleum, chemical industry and other fields.

[0027] In the process of manufacturing nickel-based corrosion-resistant alloy, a graphene-coated tungsten carbide is first prepared, and tungsten carbide is used as a raw material for dispersion, and then laser irradiation is performed. The ultra-high temperature and ultra-high pressure generated by the laser provide conditions for the change of the morphology of tungsten carbide particles, so that the tungsten carbide particles are transformed from irregular particles to regular spherical particles, and the carbon atoms on the surface of the spherical tungsten carbide particles are graphitized to form a graphene shell, which is coated on the tungsten carbide particles to obtain graphene-coated tungsten carbide; tungsten carbide itself is a material with high hardness and high melting point, and has good wear resistance and corrosion resistance. In a high temperature environment, tungsten carbide can maintain the stability of its structure and performance, and is not easy to undergo phase change or decomposition. As a two-dimensional material, graphene has It has extremely high thermal stability and mechanical strength. When it is used as a coating, it can effectively isolate the tungsten carbide core from direct contact with the external environment and reduce the direct thermal shock of high temperature on tungsten carbide. Therefore, the core-shell structure formed by graphene coating tungsten carbide has a unique synergistic effect. The graphene layer acts as an outer barrier to protect the inner tungsten carbide from high temperature and corrosion, while the tungsten carbide core provides strength and hardness support. This core-shell structure can play its respective advantages when subjected to stress and jointly resist high-temperature creep. The graphene layer disperses stress and prevents crack propagation, while the tungsten carbide core maintains its hardness and stability to prevent creep deformation of the material. Adding it to nickel-based corrosion-resistant alloys can effectively enhance their creep resistance.

[0028] In the process of manufacturing nickel-based corrosion-resistant alloy, a performance enhancer is also prepared. First, maleic anhydride and diethanolamine are reacted, and maleic anhydride reacts with the secondary amine group or hydroxyl group on the diethanolamine to form an intermediate product A containing carboxyl, hydroxyl and alkenyl groups. Then, mercaptopropionic acid and pentaerythritol are reacted, and the carboxyl group on the mercaptopropionic acid reacts with the hydroxyl group on the pentaerythritol to form an intermediate product B containing four mercapto groups. Then, the intermediate product A and the intermediate product B react, and the alkenyl group on the intermediate product A reacts with the mercapto group on the intermediate product B to undergo a click chemical reaction, thereby connecting a large number of hydroxyl groups and carboxyl groups to the skeleton of the intermediate product B to obtain a performance enhancer. Energy enhancers can effectively adsorb onto the raw material particles of nickel-based corrosion-resistant alloys by utilizing the abundant hydroxyl and carboxyl groups in their molecular structure, which can reduce the surface energy of the particles or cause dislocation migration of the near-surface layer lattices, resulting in point or line defects, thereby reducing the strength and hardness of the particles. At the same time, it prevents the closure of new cracks and promotes crack propagation, allowing the particles to be fully refined, promoting the heterogeneous nucleation process in the alloy melt, increasing the number of crystal nuclei, thereby refining the grain structure of the alloy, improving the density and mechanical properties of the alloy, thereby improving the overall performance of the alloy, and further enhancing the mechanical properties and creep resistance of the nickel-based corrosion-resistant alloy. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Embodiment 1:

[0031] This embodiment is a method for manufacturing a nickel-based corrosion-resistant alloy resistant to high temperature creep, comprising the following steps:

[0032] Step S1: 0.15 g of tungsten carbide and 50 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 25 min at an ultrasonic power of 300 W. Then, the reaction was stirred at a temperature of 25 ° C and a stirring rate of 300 r / min for 1 h. After the reaction was completed, the reaction product was irradiated with a KrF excimer laser at an energy density of 0.8 J / cm 2 , irradiate for 20 minutes at a laser frequency of 10 Hz, then centrifuge, wash the precipitate twice with a 70% volume fraction ethanol solution, then place it in a vacuum drying oven and dry it at 70°C for 3 hours to obtain graphene-coated tungsten carbide;

[0033] Step S2: 10 mmol of maleic anhydride, 10 mmol of diethanolamine and 0.01 g of p-toluenesulfonic acid were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at 25° C. and a stirring rate of 300 r / min for 20 min, then heated to 60° C. and continued to stir for reaction for 1 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain an intermediate product A;

[0034] Step S3: 45 mmol of mercaptopropionic acid, 10 mmol of pentaerythritol, 0.03 g of p-toluenesulfonic acid and 50 mL of toluene were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred at 25° C. and a stirring rate of 300 r / min for 15 min, and then the mixture was heated to 90° C. and stirred for 6 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an intermediate product B;

[0035] Step S4: 40 mmol of intermediate product A, 10 mmol of intermediate product B, 45 mmol of triethylamine and 80 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the temperature was raised to reflux and the stirring reaction was continued for 2 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain a performance enhancer;

[0036] Step S5: weigh 50 parts of nickel powder, 17 parts of chromium powder, 24 parts of iron powder, 22 parts of molybdenum powder, 1 part of graphene-coated tungsten carbide, 0.6 parts of titanium powder, 0.2 parts of aluminum powder and 0.1 parts of silicon powder according to weight parts for later use;

[0037] Step S6: uniformly mixing nickel powder, chromium powder, iron powder, molybdenum powder, graphene-coated tungsten carbide, titanium powder, aluminum powder and silicon powder to obtain a mixed powder material;

[0038] Step S7: adding 10 kg of mixed powder, 0.2 kg of performance enhancer and 20 L of anhydrous ethanol into a ball mill, ball milling for 2 h at a ball milling rate of 300 r / min, and then drying to obtain a ball milled powder;

[0039] Step S8: melting the ball-milled powder material, and then casting to form an ingot;

[0040] Step S9: heating the ingot at 1150° C. for 8 h, and then hot-rolling and forging to obtain a nickel-based corrosion-resistant alloy resistant to high-temperature creep.

[0041] Embodiment 2:

[0042] This embodiment is a method for manufacturing a nickel-based corrosion-resistant alloy resistant to high temperature creep, comprising the following steps:

[0043] Step S1: 0.15 g of tungsten carbide and 55 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 30 min at an ultrasonic power of 325 W. Then, the reaction was stirred at a temperature of 28 ° C and a stirring rate of 350 r / min for 1.5 h. After the reaction was completed, the reaction product was irradiated with a KrF excimer laser at an energy density of 0.8 J / cm 2 , irradiate for 25 min at a laser frequency of 10 Hz, then centrifuge, wash the precipitate twice with a 75% volume fraction ethanol solution, then place it in a vacuum drying oven and dry it at 72°C for 4 h to obtain graphene-coated tungsten carbide;

[0044] Step S2: 10 mmol of maleic anhydride, 10 mmol of diethanolamine and 0.02 g of p-toluenesulfonic acid were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, then the temperature was raised to 62° C. and the stirring reaction was continued for 1 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain an intermediate product A;

[0045] Step S3: 48 mmol of mercaptopropionic acid, 10 mmol of pentaerythritol, 0.05 g of p-toluenesulfonic acid and 55 mL of toluene were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 20 min, then heated to 92° C. and continued to stir for reaction for 7 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an intermediate product B;

[0046] Step S4: 42 mmol of intermediate product A, 10 mmol of intermediate product B, 48 mmol of triethylamine and 90 mL of anhydrous tetrahydrofuran were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then the mixture was heated to reflux and continued to stir for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filtrate was rotary evaporated to remove the solvent to obtain a performance enhancer;

[0047] Step S5: weigh 52 parts of nickel powder, 19 parts of chromium powder, 26 parts of iron powder, 24 parts of molybdenum powder, 5 parts of graphene-coated tungsten carbide, 0.9 parts of titanium powder, 0.5 parts of aluminum powder and 0.3 parts of silicon powder according to weight parts, and set aside;

[0048] Step S6: uniformly mixing nickel powder, chromium powder, iron powder, molybdenum powder, graphene-coated tungsten carbide, titanium powder, aluminum powder and silicon powder to obtain a mixed powder material;

[0049] Step S7: adding 10 kg of mixed powder, 1.0 kg of performance enhancer and 25 L of anhydrous ethanol into a ball mill, and ball milling for 2.5 h at a ball milling rate of 350 r / min, and then drying to obtain a ball milled powder;

[0050] Step S8: melting the ball-milled powder material, and then casting to form an ingot;

[0051] Step S9: heating the ingot at 1175° C. for 9 hours, and then hot-rolling and forging to obtain a nickel-based corrosion-resistant alloy resistant to high-temperature creep.

[0052] Embodiment 3:

[0053] This embodiment is a method for manufacturing a nickel-based corrosion-resistant alloy resistant to high temperature creep, comprising the following steps:

[0054] Step S1: 0.15 g of tungsten carbide and 60 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 35 min at an ultrasonic power of 350 W. Then, the reaction was stirred at a temperature of 30 ° C and a stirring rate of 400 r / min for 1.5 h. After the reaction was completed, the reaction product was irradiated with a KrF excimer laser at an energy density of 0.8 J / cm 2 , irradiate for 30 min at a laser frequency of 10 Hz, then centrifuge, wash the precipitate three times with an ethanol solution with a volume fraction of 80%, then place it in a vacuum drying oven and dry it at a temperature of 75°C for 5 h to obtain graphene-coated tungsten carbide;

[0055] Step S2: 10 mmol of maleic anhydride, 10 mmol of diethanolamine and 0.03 g of p-toluenesulfonic acid were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, then heated to 65° C. and continued to stir for reaction for 1.5 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain an intermediate product A;

[0056] Step S3: 50 mmol of mercaptopropionic acid, 10 mmol of pentaerythritol, 0.07 g of p-toluenesulfonic acid and 60 mL of toluene were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred at 30° C. and a stirring rate of 400 r / min for 25 min, and then the mixture was heated to 95° C. and stirred for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an intermediate product B;

[0057] Step S4: 45 mmol of intermediate product A, 10 mmol of intermediate product B, 50 mmol of triethylamine and 100 mL of anhydrous tetrahydrofuran are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the temperature is raised to reflux and the stirring reaction is continued for 3 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a performance enhancer;

[0058] Step S5: weigh 55 parts of nickel powder, 21 parts of chromium powder, 28 parts of iron powder, 26 parts of molybdenum powder, 9 parts of graphene-coated tungsten carbide, 1.2 parts of titanium powder, 0.8 parts of aluminum powder and 0.5 parts of silicon powder according to weight parts for later use;

[0059] Step S6: uniformly mixing nickel powder, chromium powder, iron powder, molybdenum powder, graphene-coated tungsten carbide, titanium powder, aluminum powder and silicon powder to obtain a mixed powder material;

[0060] Step S7: adding 10 kg of mixed powder, 1.8 kg of performance enhancer and 30 L of anhydrous ethanol into a ball mill, and ball milling for 3 h at a ball milling rate of 400 r / min, and then drying to obtain a ball milled powder;

[0061] Step S8: melting the ball-milled powder material, and then casting to form an ingot;

[0062] Step S9: heating the ingot at 1200° C. for 10 h, and then hot-rolling and forging to obtain a nickel-based corrosion-resistant alloy resistant to high-temperature creep.

[0063] Comparative Example 1:

[0064] This comparative example is a method for manufacturing a nickel-based corrosion-resistant alloy resistant to high temperature creep, comprising the following steps:

[0065] Step S1: weigh 55 parts of nickel powder, 21 parts of chromium powder, 28 parts of iron powder, 26 parts of molybdenum powder, 1.2 parts of titanium powder, 0.8 parts of aluminum powder and 0.5 parts of silicon powder according to weight parts, and set aside;

[0066] Step S2: uniformly mixing nickel powder, chromium powder, iron powder, molybdenum powder, titanium powder, aluminum powder and silicon powder to obtain a mixed powder material;

[0067] Step S3: adding 10 kg of the mixed powder material and 30 L of anhydrous ethanol into a ball mill, ball milling for 3 h at a ball milling rate of 400 r / min, and then drying to obtain a ball-milled powder material;

[0068] Step S4: melting the ball-milled powder material, and then casting to form an ingot;

[0069] Step S5: heating the ingot at 1200° C. for 10 h, and then hot-rolling and forging to obtain a nickel-based corrosion-resistant alloy resistant to high-temperature creep.

[0070] Comparative Example 2:

[0071] This comparative example is a method for manufacturing a nickel-based corrosion-resistant alloy resistant to high temperature creep, comprising the following steps:

[0072] Step S1: 0.15 g of tungsten carbide and 60 mL of anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 35 min at an ultrasonic power of 350 W. Then, the reaction was stirred at a temperature of 30 ° C and a stirring rate of 400 r / min for 1.5 h. After the reaction was completed, the reaction product was irradiated with a KrF excimer laser at an energy density of 0.8 J / cm 2 , irradiate for 30 min at a laser frequency of 10 Hz, then centrifuge, wash the precipitate three times with an ethanol solution with a volume fraction of 80%, then place it in a vacuum drying oven and dry it at a temperature of 75°C for 5 h to obtain graphene-coated tungsten carbide;

[0073] Step S2: weigh 55 parts of nickel powder, 21 parts of chromium powder, 28 parts of iron powder, 26 parts of molybdenum powder, 9 parts of graphene-coated tungsten carbide, 1.2 parts of titanium powder, 0.8 parts of aluminum powder and 0.5 parts of silicon powder according to weight parts, and set aside;

[0074] Step S3: uniformly mixing nickel powder, chromium powder, iron powder, molybdenum powder, graphene-coated tungsten carbide, titanium powder, aluminum powder and silicon powder to obtain a mixed powder material;

[0075] Step S4: adding 10 kg of the mixed powder material and 30 L of anhydrous ethanol into a ball mill, ball milling for 3 h at a ball milling rate of 400 r / min, and then drying to obtain a ball-milled powder material;

[0076] Step S5: melting the ball-milled powder material, and then casting to form an ingot;

[0077] Step S6: heating the ingot at 1200° C. for 10 h, and then hot-rolling and forging to obtain a nickel-based corrosion-resistant alloy resistant to high-temperature creep.

[0078] Comparative Example 3:

[0079] This comparative example is a method for manufacturing a nickel-based corrosion-resistant alloy resistant to high temperature creep, comprising the following steps:

[0080] Step S1: 10 mmol maleic anhydride, 10 mmol diethanolamine and 0.03 g p-toluenesulfonic acid were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, then heated to 65° C. and continued to stir for reaction for 1.5 h. After the reaction was completed, the reaction product was cooled to room temperature to obtain an intermediate product A;

[0081] Step S2: 50 mmol of mercaptopropionic acid, 10 mmol of pentaerythritol, 0.07 g of p-toluenesulfonic acid and 60 mL of toluene were added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and the mixture was stirred at 30° C. and a stirring rate of 400 r / min for 25 min, and then the mixture was heated to 95° C. and stirred for 8 h. After the reaction was completed, the reaction product was cooled to room temperature, and then the solvent was removed by rotary evaporation to obtain an intermediate product B;

[0082] Step S3: 45 mmol of intermediate product A, 10 mmol of intermediate product B, 50 mmol of triethylamine and 100 mL of anhydrous tetrahydrofuran are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the temperature is raised to reflux and the stirring reaction is continued for 3 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered, and the filtrate is rotary evaporated to remove the solvent to obtain a performance enhancer;

[0083] Step S4: weigh 55 parts of nickel powder, 21 parts of chromium powder, 28 parts of iron powder, 26 parts of molybdenum powder, 1.2 parts of titanium powder, 0.8 parts of aluminum powder and 0.5 parts of silicon powder according to weight parts, and set aside;

[0084] Step S5: uniformly mixing nickel powder, chromium powder, iron powder, molybdenum powder, titanium powder, aluminum powder and silicon powder to obtain a mixed powder material;

[0085] Step S6: adding 10 kg of mixed powder, 1.8 kg of performance enhancer and 30 L of anhydrous ethanol into a ball mill, and ball milling for 3 h at a ball milling rate of 400 r / min, and then drying to obtain a ball milled powder;

[0086] Step S7: melting the ball-milled powder material, and then casting to form an ingot;

[0087] Step S8: heating the ingot at 1200° C. for 10 h, and then hot-rolling and forging to obtain a nickel-based corrosion-resistant alloy resistant to high-temperature creep.

[0088] The nickel-based corrosion-resistant alloys of Examples 1-3 and Comparative Examples 1-3 were tested for performance, and the test results are as follows:

[0089]

[0090] Among them, the creep strain was tested after creeping for 6 h at 1100°C / 130 MPa;

[0091] Referring to the data in the above table, the nickel-based corrosion-resistant alloy coated with graphene tungsten carbide and performance enhancer has excellent mechanical properties and high-temperature creep resistance.

[0092] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0093] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A nickel-based corrosion-resistant alloy resistant to high temperature creep, characterized in that: It comprises the following components in parts by weight: 50-55 parts of nickel powder, 17-21 parts of chromium powder, 24-28 parts of iron powder, 22-26 parts of molybdenum powder, 1-9 parts of graphene-coated tungsten carbide, 0.6-1.2 parts of titanium powder, 0.2-0.8 parts of aluminum powder and 0.1-0.5 parts of silicon powder; A method for manufacturing a nickel-based corrosion-resistant alloy resistant to high temperature creep comprises the following steps: Step 1: Weigh 50-55 parts of nickel powder, 17-21 parts of chromium powder, 24-28 parts of iron powder, 22-26 parts of molybdenum powder, 1-9 parts of graphene-coated tungsten carbide, 0.6-1.2 parts of titanium powder, 0.2-0.8 parts of aluminum powder and 0.1-0.5 parts of silicon powder according to weight parts, and set aside; Step 2: Evenly mix nickel powder, chromium powder, iron powder, molybdenum powder, graphene-coated tungsten carbide, titanium powder, aluminum powder and silicon powder to obtain a mixed powder material; Step 3: Add the mixed powder, performance enhancer and anhydrous ethanol into a ball mill, and mill for 2-3 hours at a ball milling rate of 300-400 r / min, and then dry to obtain a ball-milled powder; Step 4: Melt the ball mill powder and then cast it to form an ingot; Step 5: heating the ingot at a temperature of 1150-1200° C. for 8-10 hours, and then hot-rolling and forging to obtain a nickel-based corrosion-resistant alloy resistant to high temperature creep; Wherein, the graphene-coated tungsten carbide is prepared by the following steps: Tungsten carbide and anhydrous ethanol were added to a three-necked flask equipped with a stirrer and a thermometer, and ultrasonically dispersed for 25-35 minutes at an ultrasonic power of 300-350 W. Then, the reaction was stirred for 1-1.5 hours at a temperature of 25-30 ° C and a stirring rate of 300-400 r / min. After the reaction was completed, the reaction product was irradiated with a KrF excimer laser at an energy density of 0.8 J / cm 2 , irradiate for 20-30 minutes at a laser frequency of 10 Hz, then centrifuge, wash the precipitate with an ethanol solution for 2-3 times, then place it in a vacuum drying oven, and dry it at a temperature of 70-75°C for 3-5 hours to obtain graphene-coated tungsten carbide; the dosage ratio of the tungsten carbide to anhydrous ethanol is 0.15g:50-60mL; the volume fraction of the ethanol solution is 70-80%; Wherein, the performance enhancer is prepared by the following steps: Step a1: maleic anhydride, diethanolamine and p-toluenesulfonic acid are added to a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, and stirred for reaction at a temperature of 25-30°C and a stirring rate of 300-400 r / min for 20-30 min, and then the temperature is raised to 60-65°C and the stirring reaction is continued for 1-1.5 h. After the reaction is completed, the reaction product is cooled to room temperature to obtain an intermediate product A; the amount ratio of maleic anhydride, diethanolamine and p-toluenesulfonic acid is 10 mmol: 10 mmol: 0.01-0.03 g; Step a2: adding mercaptopropionic acid, pentaerythritol, p-toluenesulfonic acid and toluene into a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, stirring the mixture for 15-25 min at a temperature of 25-30° C. and a stirring rate of 300-400 r / min, then heating the mixture to 90-95° C. and continuing to stir the mixture for 6-8 h. After the reaction is completed, cooling the reaction product to room temperature, and then removing the solvent by rotary evaporation to obtain an intermediate product B; the amount ratio of mercaptopropionic acid, pentaerythritol, p-toluenesulfonic acid and toluene is 45-50 mmol: 10 mmol: 0.03-0.07 g: 50-60 mL; Step a3: add intermediate product A, intermediate product B, triethylamine and anhydrous tetrahydrofuran to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, introduce nitrogen protection, stir and react for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heat to reflux and continue stirring and reacting for 2-3 hours. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, and rotary evaporate the filtrate to remove the solvent to obtain a performance enhancer; the amount ratio of the intermediate product A, intermediate product B, triethylamine and anhydrous tetrahydrofuran is 40-45mmol:10mmol:45-50mmol:80-100mL.

2. A nickel-based corrosion-resistant alloy resistant to high temperature creep according to claim 1, characterized in that: The dosage ratio of the mixed powder material, the performance enhancer and the anhydrous ethanol is 10kg: 0.2-1.8kg: 20-30L.

Citation Information

Patent Citations

  • Preparation method of nickel-based high-temperature-resistant alloy material

    CN111057907A

  • High-wear-resistance nickel-based alloy flux-cored wire and preparation method thereof

    CN116329802A